Venous thromboembolism in patients with symptomatic atherosclerosis - Piazza, Gregory; Goldhaber, Samuel Z.; Lessard, Darleen M.; Goldberg, Robert J.; Emery, Catherine; Spencer, Frederick A. (Thrombosis and Haemostasis, 2011)
Patients with atherosclerosis have an increased risk of venous thromboembolism (VTE). We studied patients in the population-based Worcester VTE Study of 1,822 consecutive patients with validated VTE to compare clinical characteristics, prophylaxis, treatment, and outcomes of VTE in patients with and without symptomatic atherosclerotic cardiovascular disease, defined as history of ischaemic heart disease, history of positive cardiac catheterisation, percutaneous coronary intervention, or coronary artery bypass graft surgery, or history of peripheral artery disease. Of the 1,818 patients with VTE, 473 (26%) had a history of symptomatic atherosclerosis. Patients with atherosclerosis were significantly older (mean age 71.9 years vs. 61.6 years) and were more likely to have immobility (57.2% vs. 46.7%), prior heart failure (36.9% vs. 10.7%), chronic lung disease (26.4% vs. 15.5%), cerebrovascular disease (18.1% vs. 9.8%), and chronic kidney disease (4.9% vs. 1.9%) (all p<0.001) compared with non-atherosclerosis patients. Thromboprophylaxis was omitted in more than one-third of atherosclerosis patients who had been hospitalised for non-VTE-related illness or had undergone major surgery within the three months prior to VTE. Patients with atherosclerosis were significantly more likely to suffer in-hospital major bleeding (7.6% vs. 3.8%, p=0.0008). In conclusion, patients with atherosclerosis and VTE are more likely to suffer a complicated hospital course. Despite a high frequency of comorbid conditions contributing to the risk of VTE, we observed a low rate of thromboprophylaxis in patients with symptomatic atherosclerosis.
Keywords: Atherosclerosis; deep-vein thrombosis; prophylaxis; pulmonary embolism; treatment; venous thromboembolism